Manufacturing Village Development for Structural Transformation: A Policy Design Study for Indonesia - Abi Fadillah; Bintang Satrio Wibowo (Journal of Business and Economics Research (JBE), 2026)
National development constitutes a constitutional mandate to achieve social welfare, as affirmed in the Preamble of the 1945 Constitution of the Republic of Indonesia. Nevertheless, Indonesia’s development trajectory has remained predominantly growth-oriented, resulting in persistent structural disparities between urban and rural areas. Although policy initiatives such as the Asta Cita framework and village fund allocation have been implemented, the economic contribution of rural areas to national Gross Domestic Product (GDP) remains limited. At the same time, the declining share of manufacturing at the national level signals emerging deindustrialization. This condition highlights the absence of an integrated rural-based industrialization model capable of driving structural transformation. This study adopts a policy design approach based on normative policy analysis and comparative institutional review. The analytical procedure involves synthesizing structural transformation theory, examining Indonesia’s regulatory framework on rural and industrial development, and reviewing selected international experiences to construct a contextually relevant policy design. The study does not employ primary or econometric data, but develops a structured policy design derived from theoretical and institutional analysis. The paper proposes the policy of a Manufacturing Village as a region-based development paradigm aimed at strengthening manufacturing activities in rural areas through the integration of bottom-up participation and top-down coordination. Contribution of this research lies in extending structural transformation discourse toward a village-level governance framework and providing an operational institutional architecture that connects national industrial policy with rural administrative systems. The proposed framework is expected to enhance rural value-added production, expand non-agricultural employment, reduce regional disparities, and support inclusive and sustainable structural transformation in Indonesia.